(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The antibiotics are sold without prescription in South Haryana at the chemist shops. The practice is more pronounced in rural areas and low income communities. Antibiotics are illegally purchase without medical prescriptions and very little effort. The role of pharmacists in contributing to healthcare remains debatable. In South Haryana, there are deficiencies in the professional practice. Community pharmacists are observed retailers and businessman than healthcare providers. Self-medication of antibiotics is a universal problem around the globe. The practice cuts gender, culture, age, social status and occupation. Unprescribed use of antibiotics increases bacterial resistance and drug reactions. It also creates adverse effect on human body. The aim of the paper is to discuss unprescribed use of antibiotics in South Haryana. It will discuss the concept of self-medication probable problems, solutions and resistance of microbes.